Utilization of iron fillings solid waste for optimum biodiesel production - El-Bayoumy, Fady I.; Osman, Ahmed I.; Rooney, David W.; Roushdy, Mai H. (Frontiers in Chemistry, 2024)
This study explores the innovative application of iron filings solid waste, a byproduct from mechanical workshops, as a heterogeneous catalyst in the production of biodiesel from waste cooking oil. Focusing on sustainability and waste valorization, the research presents a dual-benefit approach: addressing the environmental issue of solid waste disposal while contributing to the renewable energy sector. Particle size distribution analysis, X-ray diffraction (XRD), scanning electron microscopy (SEM), X-ray fluorescence (XRF), Thermal analysis (TG-DTA), and FTIR analysis were used to characterize the iron filings. The response surface methodology (RSM) was used to guide a series of experiments that were conducted to identify the optimum transesterification settings. Important factors that greatly affect the production of biodiesel are identified by the study, including catalyst loading, reaction time, methanol-to-oil ratio, reaction temperature, and stirring rate. The catalyst proved to be successful as evidenced by the 96.4% biodiesel conversion efficiency attained under ideal conditions. The iron filings catalyst’s reusability was evaluated, demonstrating its potential for numerous applications without noticeably decreasing activity. This work offers a road towards more environmentally friendly and sustainable chemical processes in energy production by making a strong argument for using industrial solid waste as a catalyst in the biodiesel manufacturing process.